EXPRESSION OF THE CATEGORY OF NUMBERS IN ARABIC NOUNS IN THE WORKS OF ALISHER NAVOI AND MAHMUDHOJA BEHBUDI - M.Tojiboeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article reveals the distinctive features of the number category in Arabic using examples from the works of Alisher Navoi and Mahmudkhoja Behbudi.